The SAGE international encyclopedia of mass media and society - Merskin, Debra L. (Los Angeles, CA : SAGE Publications, Inc., 2020)
The SAGE International Encyclopedia of Mass Media and Society discusses media around the world in their varied forms - newspapers, magazines, radio, television, film, books, music, websites, social media, mobile media - and describes the role of each in both mirroring and shaping society. This encyclopedia provides a thorough overview of media within social and cultural contexts, exploring the development of the mediated communication industry, mediated communication regulations, and societal interactions and effects. This reference work will look at issues such as free expression and government regulation of media; how people choose what media to watch, listen to, and read; and how the influence of those who control media organizations may be changing as new media empower previously unheard voices. The role of media in society will be explored from international, multidisciplinary perspectives via approximately 700 articles drawing on research from communication and media studies, sociology, anthropology, social psychology, politics, and business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Mass media -- Social aspects -- Encyclopedias